'I Want to Give Something Back': Social Support and Reciprocity in the Lives of Young Refugees - Schmitt, Caroline (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2021)
This article analyzes the support relationships of 10 asylum-seeking young people who fled to Germany between 2010 and 2015. It highlights their wish for reciprocity as a need in their country of destination and expands upon Sahlin’s typology of reciprocal relationships (generalized, balanced, and negative reciprocity) by the type of “refused reciprocity.” “Refused reciprocity” occurs when people are keen to reciprocate for support they have received, but they live in environments that restrict their agency. The article argues that participation means not only provision of support, but creation of opportunities for people to experience themselves as self-effective actors. They become self-effective when they can cope successfully with new and difficult situations on their own.